P-glycoprotein activation by 1-(propan-2-ylamino)-4-propoxy-9H-thioxanthen-9-one (TX5) in rat distal ileum: ex vivo and in vivo studies - Rocha-Pereira, Carolina (2020)
In vitro studies showed that 1-(propan-2-ylamino)-4-propoxy-9H-thioxanthen-9-one (TX5) increases P-glycoprotein (P-gp) expression and activity in Caco-2 cells, preventing xenobiotic toxicity. The present study aimed at investigating TX5 effects on P-gp expression/activity using Wistar Han rats: a) in vivo, evaluating intestinal P-gp activity; b) ex vivo, evaluating P-gp expression in ileum brush border membranes (BBM) and P-gp activity in everted intestinal sacs; c) ex vivo, evaluating P-gp activity in everted intestinal sacs of the distal and proximal ileum. TX5 (30 mg/kg, b.w.), gavage, activated P-gp in vivo, given the significant decrease in the AUC of digoxin (0.25 mg/kg, b.w.). The efflux of rhodamine 123 (300 μM), a P-gp fluorescent substrate, significantly increased in TX5-treated everted sacs from the distal portion of the rat ileum, when P-gp activity was evaluated in the presence of TX5 (20 μM), an effect abolished by the P-gp inhibitor verapamil (100 μM). No increases on P-gp expression or activity were found in TX5-treated BBM of the distal ileum and everted distal sacs, respectively, 24 h after TX5 (10 mg/kg, b.w.) administration. In vivo, no differences were found on digoxin portal concentration between control (digoxin 0.025 mg/kg, b.w., intraduodenal) and TX5-treated (digoxin+TX5 20 μM, intraduodenal) rats. The observed discrepancies in digoxin results can be related to differences in TX5 dose administered and used methodologies. Thus, the results show that TX5 activates P-gp at the distal portion of the rat ileum, and, at the higher dose tested (30 mg/kg, b.w.), seems to modulate in vivo the AUC of P-gp substrates.